Needs Analysis of Uterine Involution Phantoom - Novianti, Lily; Komariah, Nurul (Journal of Midwifery and Nursing, 2024)
This study aims to determine whether the development of a uterine involution phantom is needed in the Midwifery Department, Ministry Health Polytechnic of Palembang. This research is quantitative research with a research instrument in the form of a questionnaire. Filling out the questionnaire was carried out by fourth semester students who had passed the postpartum midwifery care and breastfeeding course. Almost all the statements the majority of respondents strongly agree. In the statement “The phantom needed is a phantom that can be palpated at the height of the uterine fundus according to the postpartum physiological age”. In the statement "In carrying out the practice of examining postpartum mothers' uterine involution in the laboratory, I need a mannequins/phantom media" 18 respondents (60%) stated that they strongly agree. Likewise, with the statement "As a prospective midwife, it is important for me to carry out physical examinations on postpartum women," there were 18 respondents (60%) who strongly agreed. Phantoom is needed for practical learning in the laboratory. Uterine involution phantoom that students need is a phantoom that can be palpated at the height of the uterine fundus, not just imagined